Postsynaptic Action Potentials Are Required for Nitric-Oxide-Dependent Long-Term Potentiation in CA1 Neurons of Adult GluR1 Knock-Out and Wild-Type Mice - Phillips, Keith G. (Society for Neuroscience, 2008)
Neocortical long-term potentiation (LTP) consists of both presynaptic and postsynaptic components that rely on nitric oxide (NO) and the GluR1 subunit of the AMPA receptor, respectively. In this study, we found that hippocampal LTP, induced by theta-burst stimulation in mature (>8-week-old) GluR1 knock-out mice was almost entirely NO dependent and involved both the α splice variant of NO synthase-1 and the NO synthase-3 isoforms of NO synthase. Theta-burst induced LTP was also partly NO-dependent in wild-type mice and made up ∼50% of the potentiation 2 h after tetanus. Theta-burst stimulation reliably produced postsynaptic spikes, including a high probability of complex spikes. Inhibition of postsynaptic somatic spikes with intracellular QX314 or local TTX application prevented LTP in the GluR1 knock-out mice and also blocked the NO component of LTP in wild types. We conclude that theta-burst stimulation is particularly well suited to producing the postsynaptic somatic spikes required for NO-dependent LTP.